2015
DOI: 10.1177/0959683615618255
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic chronostratigraphy of late Holocene Zaca Lake, California

Abstract: We have developed a paleomagnetic secular variation (PSV) record from Zaca Lake, California, that spans the last ~3200 years. The record is derived from detailed (2 cm) sampling of core 09-1C, which is 873 cm in length. The paleomagnetic remanence is carried jointly by magnetite and greigite. The greigite appears to form in the anoxic bottom water of the lake and/or at the sediment/water interface. The paleomagnetic remanence has a very simple characteristic remanence, which demagnetizes straight to the origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
(78 reference statements)
3
12
0
Order By: Relevance
“…Early paleomagnetic studies of these rocks in Southern California (Hornafius, 1984(Hornafius, , 1994 identified magnetite as the primary detrital magnetic phase. Our rock magnetic experiments (Lund and Platzman, 2016) both confirmed the presence of magnetite and identified a remanence carrying iron sulfide phase, presumably greigite (Fe 1-X S) in varying proportions, throughout the sediment column. Temperature dependence of low field susceptibility (Lund and Platzman, 2016) and thermal demagnetization of threecomponent composite IRM (Figure 3a-e) show evidence for the presence of these two magnetic phases in most samples.…”
Section: Rock Magnetic Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Early paleomagnetic studies of these rocks in Southern California (Hornafius, 1984(Hornafius, , 1994 identified magnetite as the primary detrital magnetic phase. Our rock magnetic experiments (Lund and Platzman, 2016) both confirmed the presence of magnetite and identified a remanence carrying iron sulfide phase, presumably greigite (Fe 1-X S) in varying proportions, throughout the sediment column. Temperature dependence of low field susceptibility (Lund and Platzman, 2016) and thermal demagnetization of threecomponent composite IRM (Figure 3a-e) show evidence for the presence of these two magnetic phases in most samples.…”
Section: Rock Magnetic Resultssupporting
confidence: 66%
“…Our rock magnetic experiments (Lund and Platzman, 2016) both confirmed the presence of magnetite and identified a remanence carrying iron sulfide phase, presumably greigite (Fe 1-X S) in varying proportions, throughout the sediment column. Temperature dependence of low field susceptibility (Lund and Platzman, 2016) and thermal demagnetization of threecomponent composite IRM (Figure 3a-e) show evidence for the presence of these two magnetic phases in most samples. In the IRM experiments, the remanent magnetization was found to reside predominantly in the low and medium coercivity fractions, which have similar unblocking characteristics.…”
Section: Rock Magnetic Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…Moreover, such efforts have been summarized as PSV reference curves [ Snowball et al ., ; St‐Onge et al ., ; Turner and Thompson , ]. Because their continuous records are believed to be robust regionally, they have been applied to constrain the age model of sediments, and to correlate site data in lake and marine environments [ Henkel et al ., ; Lund and Platzman , ; Ólafsdóttir et al ., ; Sagnotti et al ., ; Stoner et al ., ; Yang et al ., ; Usapkar et al ., ]. This record is unique for stratigraphic correlations and for use as a dating tool to synchronize the local environments simultaneously to a detailed scale.…”
Section: Introductionmentioning
confidence: 99%